2011
DOI: 10.1016/j.jinsphys.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein expression during stress and diapause in the marine copepod Calanus finmarchicus

Abstract: Graphical Abstract Research HighlightsWe identified 8 heat shock proteins (3 small Hsps, 4 Hsp70's, Hsp90). Hsp70a (cytosolic clade) and Hsp21, and Hsp22 were induced by handling stress. Hsp70a expression was elevated in shallow, active animals. Hsp22 expression was elevated in deep, diapausing animals. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 *Research highlights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 64 publications
2
65
0
2
Order By: Relevance
“…High heavy metal concentrations are known to affect the rotifer community (Cecchine and Snell 1999;Weisse et al 2013). Additionally, the diapause pattern observed in different organisms as response to arsenic might be a general response to stressors (Aruda et al 2011). Nevertheless, a full assessment of fitness including the performance of individuals hatched from surviving eggs would be required to get further insight on this question.…”
Section: Discussionmentioning
confidence: 99%
“…High heavy metal concentrations are known to affect the rotifer community (Cecchine and Snell 1999;Weisse et al 2013). Additionally, the diapause pattern observed in different organisms as response to arsenic might be a general response to stressors (Aruda et al 2011). Nevertheless, a full assessment of fitness including the performance of individuals hatched from surviving eggs would be required to get further insight on this question.…”
Section: Discussionmentioning
confidence: 99%
“…Aruda et al (2011) found that the heat shock proteins, hsp70a, hsp21, and hsp22, had significantly higher expression 3 h after handling with a plankton net, but did not find any significant differences 2 h after exposure. Rahlff et al (2017) found significant changes in expression of hsp70 in response to handling, which was reduced to negligible levels after 24 h. These prior studies suggest that the expression of hsp70 peaks within 24 h after stress exposure, and may explain why we did not observe an increase in expression level of this gene 24 h after handling stress.…”
Section: Discussionmentioning
confidence: 76%
“…Experimentally-induced and handling-related stress has been extensively studied in larger crustaceans (Fotedar and Evans, 2011). To our knowledge, only a few studies, e.g., Aruda et al (2011) and Rahlff et al (2017), have examined handling stress in copepods with targeted methods, which entail the evaluation of specific transcriptional biomarkers selected to evaluate certain stressors, typically by real-time quantitative PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive expression of these hsps could be explained by multiple homologues within hsp families in Calanus spp. and their differential regulation under various stresses (Aruda et al, 2011;Smolina et al, 2015;Voznesensky et al, 2004). Therefore, additional whole transcriptome profiling would be beneficial and may result in detection of both populationspecific and population-universal molecular processes in response to stress.…”
Section: Discussionmentioning
confidence: 99%